2020
DOI: 10.1155/2020/1396705
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Risk Factors for Urinary Tract Infection in Patients with Intracranial Cerebral Hemorrhage

Abstract: Objective. This study aimed to explore the risk factors of urinary tract infection (UTI) in patients with intracranial cerebral hemorrhage (ICH). Design. This is a retrospective study, and a total of 77 patients with ICH consecutively admitted to the First Affiliated Hospital of USTC (Anhui Provincial Hospital, Hefei, China) during the period of August 2015 to August 2017 were included. The patients were divided into an UTI group (24 cases) and a non-UTI group (53 cases); patients with UTI were diagnosed accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The most common and important complication is the CAUTI. It is also one of the most common infections in the world [ 3 , 4 ]. CAUTI not only affects the success rate of patient treatment, but is also the main reason for the prolonged hospitalization time and the substantial increase in hospitalization costs [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common and important complication is the CAUTI. It is also one of the most common infections in the world [ 3 , 4 ]. CAUTI not only affects the success rate of patient treatment, but is also the main reason for the prolonged hospitalization time and the substantial increase in hospitalization costs [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study suggested that laboratory results collected on the 2nd day of admission were also related, including higher interleukin-6, and lower hemoglobin ( 14 ). Moreover, postvoid residual volume >100 mL, longer length of hospital stays, prolonged duration of an indwelling catheter, higher modified Rankin scale score, higher white blood cell count, higher copeptin, and higher procalcitonin were also reported to be high-risk factors for UTI after stroke ( 6 , 8 , 9 , 13 , 15 18 , 33 35 ). Our analysis identified several features that were associated with a higher risk of UTI in ICH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lumbar puncture ( p < 0.001), urinary catheter insertion ( p < 0.001), and peripherally inserted central catheter (PICC) ( p < 0.001), which were common to see during the treatment of ICH, were also found to be risk factors associated with HAP statistically. Although these invasive procedures cannot cause HAP directly, they can suppress immune function by causing intracranial infection and urinary tract infection [ 23 , 24 ], which emphasizes the importance of safe practice, especially the management of equipment in patient care, such as the aseptic technique in catheter use. Interestingly, hematoma drainage tube insertion was found to be a protective factor associated with HAP ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%